Alleviate Effect of Pomegranate Peel Extract in Ameliorating Fluoride-Induced Cytotoxicity, Oxidative Stress in Tetrahymena pyriformis Model - Sabraoui, Talal; Grina, Fatiha; Khider, Taleb; Nasser, Boubker; Eddoha, Rabiaa; Moujahid, Abderahman; Benbachir, Maryem; Essamadi, Abdelkhalid (Biointerface Research in Applied Chemistry, 2022)
Fluoride is a major oligo element found in nature, at excessive amounts can cause enormous harm in mammalian cells. Fruits peel, considered most often as a waste of juice processing, could play an important role in attenuating metal cytotoxicity. The present study evaluated the effect of pomegranate peel (Punica granatum. L) methanolic extract (PPE) on the Fluoride-induced toxicity and redox status in the protozoa Tetrahymena pyriformis. Polyphenols of peel extract were extracted using methanol and characterized by spectrophotometric methods, total phenolic content (TPC), total flavonoids content (TFC), and in vitro, antioxidant properties were assessed using the Folin-Ciocalteu method and DPPH, ABTS, and FRAP. Pomegranate peel is a rich source of phenolic compounds TP (223.21 +/- 15 mg GAE/g dw), TF (52.12 +/- 1.36 mg Qu/g dw) and showed high antioxidant properties DPPH (EC50 0.043 +/- 0.06 mg/ml), ABTS (EC50 0.06 +/- 0.01 mg/ml) and FRAP (1.47 +/- 0.01 mg AA equivalents/g dw). Cells were incubated with fluoride alone and in combination with PPE. NaF (0.8 mM) significantly decreased the cell viability, induced oxidative stress by decreasing antioxidants enzyme activities, and increased intracellular fluoride content. Treatment with NaF in combination with PPE decreases CAT, SOD, and GPx activities and alleviates GSH content. These findings suggest that pomegranate peel biomolecules may have a protective effect against fluoride induced-toxicity.
CRIS-Team WoS Importer:2021-09-03

Determination of Punicalagins Content, Metal Chelating, and Antioxidant Properties of Edible Pomegranate (Punica granatum L) Peels and Seeds Grown in Morocco - Sabraoui, Talal; Khider, Taleb; Nasser, Boubker; Eddoha, Rabiaa; Moujahid, Abderrahman; Benbachir, Maryam; Essamadi, Abdelkhalid (International Journal of Food Science, 2020)
Pomegranate (Punica granatum L) is widely cultivated in the Mediterranean countries especially in Morocco. Pomegranate peel and seed contain considerable amounts of phenolic compounds with antioxidant activity. The aim of the present study was to phytochemically characterize the pomegranate peels and seeds obtained from three Moroccan provinces, using UHPLC-DAD. In addition, total phenolic content (TPC), total flavonoid contents (TFC), and metal chelating of pomegranate peel were also evaluated. The results showed that pomegranate peel possesses the highest phenolic (TPC: 224.39 mg GAE/g dw) and flavonoid (TFC: 62.64 mg rutin/g dw) contents. Punicalagin-β and punicalagin-α, are the abundant compounds found in peel: 216.36±9.94 mg/g, 154.94±5.21 mg/g, respectively. Pomegranate peels showed significantly (p<0.05) high antioxidant activity 1-diphenyl-2-picrylhydrazyl (DPPH) EC50: 42.71±0.04 μg/mL, 2.2′-Azino-bis(3-Ethylbenzothiazoline-6-Sulfonic Acid) (ABTS) EC50: 62.15±0.01 μg/mL), and chelating activity (FRAP 1.85±0.00 mg ascorbic acid equivalents/100 g, Fe2+: 2.52±0.01 μmol EDTA equivalents/g dw) compared to seeds. A positive correlation between antioxidant activity and total phenolic was found. According to achieved results, high antioxidant capacity of pomegranate extracts, especially peel, shed light to further use as natural food preservatives. Pomegranate peel could be used for the fortification of food with fiber by introducing it in dietary, as well as in health applications due to its higher antioxidant capacity.
CRIS-Team Scopus Importer:2020-10-23